Pengaruh Motivasi Terhadap Kinerja Karyawan Pada PT. Bumi Pratama Usaha Jaya Bayung Lencir - Imam Suroso; Tutik Pebrianti; Aras Tulip; Vivin Afini; Indah Mawarni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
This research is conducted to find out whether these i sor not the effect and realtionship between motivation (x) and employee performance (y) at PT. Bumi Pratama Usaha Jaya In Bayung Lincir. The writer uses statistical method in analysing the data in simple linear regression analysis. Considering the results of validity and reliability test, it is stated that all statement indicators are valid and reliable, from regression analysis states that working satisfaction, commitment and working involvement have positive and significant effect on employee performance. Thus, it can be concluded that working behaviour is very identical with working satisfaction, commitment and working involvement. Their influential relationship is very positive and significan ton employee performance. Therefore, the hypothesis states working satisfaction, commitment and working involvement have positive and significant effect is accepted., this research is not good yet because of the limitation in it. Suffestion for the development of this reserch is not only done in one company but also the charecteristics of the comparison company, then if the researchdone in some different but similar companies will get the right solution.